Dynamic Mixed Models for Irregularly Observed Time Series (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
We review the conventional dynamic linear model in state-space form and give a useful generalization that admits fixed covariates to the measurement equation while treating the state vectors as time-varying random effects.